2019
DOI: 10.21203/rs.2.14491/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity and bioactivities of fungal endophytes from Distylium chinense, a rare waterlogging tolerant plant endemic to the Three Gorges Reservoir

Abstract: Background The present study focuses on diversity and biological activities of the endophytic fungal community from Distylium chinense , a rare waterlogging tolerant plant endemic to the Three Gorges Reservoir. This study has been explored the characteristics of endophytic fungi in waterlogged environment including both aquatic and terrestrial fungi, and they may produce new metabolites under complex and extreme conditions, which may possess bioactive property. Therefore, the antioxidant, antimicrobial and ant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(69 reference statements)
1
2
0
Order By: Relevance
“…Isolated fungal extracts ZA 163, LO 261, CA 041, CA 042, CA 043, FE 082, FE 084, and GE 091 from A. zygia , A. cordifolia , C. albidum , F. exasperata , and G. celosioides medicinal plants demonstrated iron chelating capability. Similar observations of antioxidant activity of endophytic fungi isolates have been reported in some medicinal plants such as Bauhinia racemosa , Distylium chinense , Euphorbia hirta , Guazoma tomentosa , Phoenix dactylifer , Phyllanthus amarus , and Senna spectabilis [ 4 , 37 – 41 ]. Our results suggest that endophytic fungi that reside in the leaves of A. ornata , A. zygia , A. cordifolia , C. albidum , F. exasperata , G. celosioides , M. thonningii , and N. laevis showed promising antioxidant activity.…”
Section: Discussionsupporting
confidence: 77%
“…Isolated fungal extracts ZA 163, LO 261, CA 041, CA 042, CA 043, FE 082, FE 084, and GE 091 from A. zygia , A. cordifolia , C. albidum , F. exasperata , and G. celosioides medicinal plants demonstrated iron chelating capability. Similar observations of antioxidant activity of endophytic fungi isolates have been reported in some medicinal plants such as Bauhinia racemosa , Distylium chinense , Euphorbia hirta , Guazoma tomentosa , Phoenix dactylifer , Phyllanthus amarus , and Senna spectabilis [ 4 , 37 – 41 ]. Our results suggest that endophytic fungi that reside in the leaves of A. ornata , A. zygia , A. cordifolia , C. albidum , F. exasperata , G. celosioides , M. thonningii , and N. laevis showed promising antioxidant activity.…”
Section: Discussionsupporting
confidence: 77%
“…However, other authors especially those focusing on the role of the members of this the genus as phytopathogens use the anamorph name on the basis that this state is the most widely applied to many plant diseases (Udayanga et al, 2011). Still many authors continue to report the two as if they were distinct and separate species adding much to the confusion (Duan et al, 2019). In this study, we have adopted to use Diaporthe as the generic name in presenting the diversity results of this study among other discussion that relate to this Genera.…”
Section: 4: Discussionmentioning
confidence: 99%
“…Even for fungal endophytes isolated from individual plant species, Diaporthe has been cited as a dominant bioactive fungal genus. For example, a study focusing on the diversity and bioactivity of endophytic fungi isolated from Distylium chinense revealed that Phomopsis sp., accounted for the highest number of bioactive fungal isolates with majority of them exhibiting antibacterial, followed by antioxidant and anticancer activities respectively (Duan et al, 2019).…”
Section: 4: Discussionmentioning
confidence: 99%